2018
DOI: 10.1021/acs.chemmater.8b00251
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Synthetic Antimicrobial with Aggregation-Induced Emissive Luminogens for Temporal Antibacterial Activity and Facile Bacteria Detection

Abstract: Aiming to address the antimicrobial resistance and environmental burdens because of the widespread indulgence in biocides, a synthetic formula of biocides with controllable antibacterial activities and biodegradable characters are encouraged for the emergence of a novel spectrum of green biocides. In this respect, a polymeric antimicrobial catiomer, with the polymeric backbone sequentially attached with the functional cationic moieties and lipophilic moieties is synthesized. The striking antibacterial potency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 43 publications
0
41
1
Order By: Relevance
“…And the amount of PGEDA in the UiO‐PGEDA was calculated to be approximately 81 wt% post polymer‐modification using thermogravimetric analysis. On the other hand, the synthetic scheme for preparation of carboxyl‐functionalized TPE was depicted in Scheme S2, Supporting Information, and the synthetic procedures were followed by our previously reported protocol . The protons of the anticipated structures were also verified in good agreement with the corresponding 1 H NMR spectra, suggesting the successful synthesis of TPE‐(COOH) 4 (Figure S2, Supporting Information).…”
Section: Methodsmentioning
confidence: 72%
“…And the amount of PGEDA in the UiO‐PGEDA was calculated to be approximately 81 wt% post polymer‐modification using thermogravimetric analysis. On the other hand, the synthetic scheme for preparation of carboxyl‐functionalized TPE was depicted in Scheme S2, Supporting Information, and the synthetic procedures were followed by our previously reported protocol . The protons of the anticipated structures were also verified in good agreement with the corresponding 1 H NMR spectra, suggesting the successful synthesis of TPE‐(COOH) 4 (Figure S2, Supporting Information).…”
Section: Methodsmentioning
confidence: 72%
“…Also, we provided evidence to show that equivalent linear polymer did not aggregate the bacteria despite being shown to bind the target D-alanyl-D-alanyl (D-Ala-D-Ala) [14] , [15] , [16] . Recently, Chen et al reported a bactericidal branched cationic polymer [17] . The central hypothesis developed on the action of these polymers has been that ligands placed at the chain ends of a highly branched polymer are available for binding to cellular targets in both the open-coil solvated form and the desolvated globular form.…”
Section: Introductionmentioning
confidence: 99%
“…Poly( N , N ′-(dimethylamino)ethyl methacrylate) (PDMAEMA) is a good cationic polymer for stabilizing AgNPs and exhibits biocidal properties by itself [ 10 , 11 , 12 ]. Functional amine groups of these polymers are often additionally quaternized to enhance their bactericidal activity [ 11 , 13 , 14 , 15 ] because they are capable of interacting with negatively charged bacterial cell surface structures. Alkyl halides are most commonly used for the quaternization reaction [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%